A rush to explore protein–ligand electrostatic interaction energy with Charger. Issue 10 (4th October 2021) - Vuković, Vedran; Leduc, Theo; Jelić-Matošević, Zoe; Didierjean, Claude; Favier, Frédérique; Guillot, Benoît; Jelsch, Christian
Abstract : Embedded within the MoProViewer program, a new code library, Charger, contains an implementation of the analytical computation of the electrostatic interaction energy based on the multipolar atom. It was used to investigate the electrostatic interaction energies of benchmark dimers and glutathione transferase–benzophenone complexes. Abstract : The mutual penetration of electron densities between two interacting molecules complicates the computation of an accurate electrostatic interaction energy based on a pseudo‐atom representation of electron densities. The numerical exact potential and multipole moment (nEP/MM) method is time‐consuming since it performs a 3D integration to obtain the electrostatic energy at short interaction distances. Nguyen et al. [(2018), Acta Cryst. A74, 524–536] recently reported a fully analytical computation of the electrostatic interaction energy (aEP/MM). This method performs much faster than nEP/MM (up to two orders of magnitude) and remains highly accurate. A new program library, Charger, contains an implementation of the aEP/MM method. Charger has been incorporated into the MoProViewer software. Benchmark tests on a series of small molecules containing only C, H, N and O atoms show the efficiency of Charger in terms of execution time and accuracy. Charger is also powerful in a study of electrostatic symbiosis between a protein and a ligand. It determines reliable protein–ligand interaction energies even when both contain S atoms. It easily estimates the individual contribution of every residue to the total protein–ligand electrostatic binding energy. Glutathione transferase (GST) in complex with a benzophenone ligand was studied due to the availability of both structural and thermodynamic data. The resulting analysis highlights not only the residues that stabilize the ligand but also those that hinder ligand binding from an electrostatic point of view. This offers new perspectives in the search for mutations to improve the interaction between the two partners. A proposed mutation would improve ligand binding to GST by removing an electrostatic obstacle, rather than by the traditional increase in the number of favourable contacts.